Induction of Somatic Embryos from Leaf and Stem Nodal Section Explants of Potato (Solanum tuberosum L.) - Iriawati, I.; Aprilianty, Fitri (Journal of Mathematical and Fundamental Sciences, 2014)
Somatic embryogenesis can be used as an alternative method to obtain high-quality potato seedlings. This research was conducted in order to evaluate: the potential of different types of explants to produce somatic mbryos;combinations of 2,4-D and BAP for somatic embryo induction; and the ability of BAP to act as growth regulator for the somatic embryo maturation process.Young leaf and stem nodal sections were cultured in MS media supplemented with 2,4-D and BAP. The developing calli were then transferred into media containing several concentrations of 2,4-D and BAP. The embryogenic calli were then transferred into media containing 1-5 Î¼M BAP. The results show that MS media containing 2,5 Î¼M 2,4-D + 5 Î¼M BAP and Î¼M 2,4-D + 0.5 Î¼M BAP were the most suitable for inducing somatic embryos from leaf explants and stem nodal section explants, respectively. The somatic embryos were well-developed in the MS media supplemented with 5 Î¼M BAP. The stem nodal section explants were able to produce a higher percentage of globular, heart and torpedo stage embryos compared with the leaf explants. Based on this research, stem nodal section explants have a high potential for producing somatic embryos induced in medium containing 1 Î¼M 2,4-D + 0.5 Î¼M BAP.